Deep Learning and IoT Enabled Real-Time Water Quality Surveillance and Decision Support Systems - B, Dr. Yuvaraj.; Josephine, Dr. D. C. Jullie; Ganesan, Dr. T.; Madhankumar, Dr.; M Ichangi, Dr. Raghavendra (International Journal of Aquatic Research and Environmental Studies, 2026)
Clean water is a basic human right and a global emergency – over 2 billion people suffer from a lack of safe drinking water. Current water quality monitoring methods require manual sampling and laboratory analysis from time to time, and involve a lot of time lag and human error in the sampling process, making them ineffective in detecting contamination events quickly. The paper proposes a complete framework which combines the Internet of Things (IoT) sensor network, multi-tier edge-fog-cloud computing structure and the latest deep learning models to provide continuous, real-time, automatic and smart water quality monitoring and intelligence decision support. The system we propose uses eight different physicochemical sensor modules (pH, DO, turbidity, EC, NO3, ORP, temp, heavy metals) at geographically distributed monitoring nodes. Readings are sent to edge gateways through quantized deep learning models which detect anomalies in less than 20 milliseconds and are transmitted using time series technology over LoRaWAN and 4G/LTE. It utilizes a novel Temporal Fusion Transformer (TFT) along with attention-augmented BiLSTM layers (TAT-BiLSTM), which are trained using more than 820,000 labeled data from five different monitoring stations over a two-year period. Experimental testing shows that the proposed TAT-BiLSTM model makes a classification accuracy of 97.3%, with a precision of 0.971 and a recall of 0.975 for five water quality index categories, outperforming all the baseline deep learning architectures by 1.7–6.5 percentage points. The system is capable of calculating a real-time composite Water Quality Index and in the event of abnormal conditions, alerts authorities with SMS/email messages via multiple levels within seconds. The decision support layer is completed by integrating with a web dashboard with GIS functionality and mobile application. From sensor reading all the way to the notification to regulatory authorities and utilities, the system's end-to-end latency is less than 25 seconds, allowing both regulatory agencies and utilities to be proactive in addressing water safety issues. The proposed framework goes beyond monitoring, and focuses on predictive intelligence and adaptive environmental management. The system not only monitors the current water quality but also continually processes the water quality data from the sensors to predict the likelihood of a contamination event occurring before it reaches critical levels. This predictive power can help regulatory bodies, water companies, and environmental organisations to take proactive action and not just a reactive one. Additionally, the framework uses state-of-the art temporal learning algorithms to identify subtle seasonal trends, periodic pollution patterns, and long-term degradation trends, which are not captured by traditional threshold monitoring systems. This makes the architecture proposed to be appropriate for both environmental surveillance and emergency response applications. The scalable and modular design is another important contribution in this work, and provides a foundation for the deployment of the monitoring network throughout rivers, lakes, reservoirs, groundwater resources, industrial discharge sites and urban drainage systems without extensive changes. As a sensor node is autonomous in its operations, and connected to each other by a shared communication infrastructure, the addition of another monitoring station to the system does not impact the system performance. Moreover, edge computing can drastically cut down on communication overhead because it can filter out anomalies and other information at the edge and only send actionable data to higher layers of processing. This helps to reduce bandwith usage and aids system reliability in remote locations with weak internet connection. The proposed architecture can be operated with energy-efficient hardware that saves power on the sensors, intelligent duty cycling, and solar-powered deployment, which reduces operational costs and maintenance demands from a sustainability point of view. The decision support platform also makes it easy to use; intuitive dashboards, historical trend visualization, automated report generation, GIS-based spatial mapping and configured alert mechanisms facilitate the easy interpretation by non-technical stakeholders. In summary, the proposed IoT–Deep Learning framework illustrates how the current artificial intelligence tools can revolutionize the traditional approach to environmental monitoring, creating an intelligent, autonomous and proactive environmental monitoring system that can help to support evidence-based policy decision, enhance public health protection and sustainable management of precious freshwater resources.
Keywords: Internet of Things (IoT), Water Quality Monitoring, Deep Learning, Edge–Fog–Cloud Computing, Temporal Fusion Transformer (TFT), Attention-Augmented BiLSTM (TAT-BiLSTM), Water Quality Index (WQI).